Anti-Arthritic Effect of Traditional Chinese Medicinal Compound Bavachalcone on Freund’s Complete Adjuvant-Induced Rheumatoid Arthritis in Rats - Xiao, Xinglei; Liu, Shanglun; Chen, Guoqing; Cao, Chen (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Oxidative stress and inflammation are suggested to be the major etiological factors for the autoimmune disease rheumatoid arthritis. Rheumatoid arthritis affects millions of individuals all over the world even though mortality rate is comparatively lower than the other autoimmune diseases it severely affects the quality life of the patients. Lack of timely and proper medical intervention could cause deformity bones leading to chronic pain, long term disability and also premature mortality. Traditional Chinese medicines are boon to treat these types of autoimmune diseases. For prolonged period these medicine were been trusted and preferred by Chinese and South Asian population. Bavachalcone is one such compound which possess diverse pharmacological properties and it proven to inhibit osteoclastogenesis activity. Objectives In our study we evaluated the ameliorative potency bavachalcone in rats induced arthritis with Freund’s complete adjuvant. Materials and Methods The weight gain and relative index of thymus and spleen were measured to assess the inflammatory response in arthritis induced rats. Paw edema volume and arthritic index was calculated to confirm the induction of arthritis in test animals. The vasoregulatory effect and impact of bavachalcone on hepatic biomarkers enzymes were assessed. The antioxidant potency of bavachalcone was determined by estimating the levels of MDA and antioxidants in arthritis induced rats. The inflammatory cytokines and the inflammatory mediators iNOS, COX-2 and NF-κB were quantified to confirm the anti-inflammatory effect of bavachalcone in arthritis induced rats. Finally the anti-arthritic potency of bavachalcone was confirmed with synovial tissue histopathological analysis. Results Bavachalcone significantly decreased the body weight, lymphatic organ relative index and paw edema volume in arthritis induced rats which was evidenced with decrease in arthritis index. It significantly decreased vasoregulators PGE2, NO and hepatic biomarker enzymes in arthritis induced rats. Bavachalcone increased the antioxidants and inhibited the synthesis of inflammatory response thereby prevented arthritis induction in rats. This was further confirmed with our histopathological results. Conclusion All together our findings suggest bavachalcone possess anti-arthritic potency and it can be formulated as drug to treat arthritis.
Keywords: Rheumatoid Arthritis; Oxidative stress; Inflammation; Anti-arthritis drug; Traditional Chinese medicine; Bavachaclone.